The Role of Mobile Phones As Effective Tools For Language Learning By Libyan EFL Learners - Safia Mujtaba Alsied (JEELS (Journal of English Education and Linguistics Studies), 2019)
The current technological era has witnessed a great advancement in the world of mobile technology. Mobiles gadgets have now turned out to be an integral element of the daily life. Given the fact that mobile devices can be used to serve a number of functions, EFL learners can utilize them regularly to enhance their process of learning and attain good learning outcome. This article intends to explore the effectiveness of using mobile phones in language learning by Libyan EFL learners. To further investigate this issue, questionnaires were administered to 151 Libyan EFL undergraduate students from the English department of Sebha University and focus group discussions (FGDs) were carried out with 18 students. The results revealed that using mobile phones in learning was effective to a great extent. Besides, the majority of Libyan EFL learners utilized their mobile phones mostly to check meaning of words, to listen to English songs and to develop reading, listening, speaking and writing skills. The findings also demonstrated that Libyan EFL learners exhibited positive perceptions towards using mobile phones in learning English.